Vibrations in Place: Sound and Language in Early Childhood Literacy Practices. Issue 4 (4th July 2018) - Gallagher, Michael; Hackett, Abigail; Procter, Lisa; Scott, Fiona
Abstract : This article explores how close attention to sound can help one to rethink literacy in early childhood education. Through an analysis of text, audio, video, and photographic data from a sound walk undertaken with a parent and a child, we make two arguments. First, contrary to skills-based approaches that abstract literacy from context, we show how literacy emerges from vibrational entanglements between bodies and places. We provide examples of how listening and sound-making unfold together in place, as sound moves between different material bodies, including children, animals, objects, buildings, and landscapes. Our analysis suggests that a wide range of sound-making and listening practices, not just those focused on words, should be valued in early childhood literacy. Second, we demonstrate how sound also transcends bodies and places through its multiplicity, ephemerality, and fluidity. We draw on the more-than-human semiotics of Eduardo Kohn to analyze how sounds operate as relational signs between human and nonhuman entities, using his ideas to move beyond human-centered, symbol-centered practices of literacy.